2022
DOI: 10.1007/s00445-022-01529-9
|View full text |Cite
|
Sign up to set email alerts
|

Paleomagnetism and rock magnetism as tools for volcanology

Abstract: Paleomagnetic and rock magnetic methods for studying volcanoes and their products have been developed since the second half of the twentieth century. These methods have been used to find tephra in sediment cores, date volcanic eruptions and deposits, determine emplacement temperatures of volcanic deposits, and estimate flow directions of dikes, lava flows, and pyroclastic flow deposits. In the twenty-first century, these techniques have steadily improved and expanded, resulting in more probing and precise stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 112 publications
0
6
0
Order By: Relevance
“…The PDC flow directions are determined from the k3 axis direction (flow direction arrows in Figs. 9a and 10), which corresponds to the fabric imbrication with respect to the basal flow plane of the deposit (e.g., Fisher et al 1993;Le Pennec et al 1998;Giordano et al 2008;LaBerge et al 2009;Cas et al 2011;Gountié Dedzo et al 2011;Lerner et al 2022). In previous studies, the shape of the AMS ellipsoids from ignimbrites is, in most cases, oblate (e.g., Ellwood 1982;Knight et al 1986;Agrò et al 2015;Ort et al 2015;Moncinhatto et al 2019).…”
Section: Pdc Flow Directions and Post-emplacement Processesmentioning
confidence: 94%
“…The PDC flow directions are determined from the k3 axis direction (flow direction arrows in Figs. 9a and 10), which corresponds to the fabric imbrication with respect to the basal flow plane of the deposit (e.g., Fisher et al 1993;Le Pennec et al 1998;Giordano et al 2008;LaBerge et al 2009;Cas et al 2011;Gountié Dedzo et al 2011;Lerner et al 2022). In previous studies, the shape of the AMS ellipsoids from ignimbrites is, in most cases, oblate (e.g., Ellwood 1982;Knight et al 1986;Agrò et al 2015;Ort et al 2015;Moncinhatto et al 2019).…”
Section: Pdc Flow Directions and Post-emplacement Processesmentioning
confidence: 94%
“…In this study, we covered some of the volcanic products from ancient (Old Krakatau) to recent (Anak Krakatau) to identify possible changes in the magma storage conditions within the Krakatau plumbing systems, as this information is required for monitoring and hazard assessment. We used a combination of petrological, geochemical, and rock magnetic analyses, which are standard tools for characterizing volcanic products (Cañón-Tapia and Pinkerton, 2000;Cinku et al, 2009;Ferré et al, 2012;Amor et al, 2019;Haag et al, 2021;Lerner et al, 2022). We also present mineralogical data, phenocryst and matrix glass compositions to reveal the magmatic plumbing systems, including the storage pressures and/or temperatures from the ancient (Old Krakatau) to the most recent (Anak Krakatau) periods.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic minerals are sensitive to magma composition and differentiation, oxidation state, pressure, and temperature (Buddington and Lindsley, 1964;Haggerty, 1991;Lanza and Meloni, 2006;Mollo et al, 2013;Liao et al, 2016;Anai et al, 2023). Therefore, previous researchers have reported that magnetic mineral characteristics, such as abundance, composition, texture, and grain size can reflect magmatic conditions and processes (Mollo et al, 2013;Lerner et al, 2022;Xu et al, 2022). The characteristics of magnetic minerals can be identified by geochemistry, petrology, and rock magnetic methods.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic analyses of oriented samples may also enable the identification and interpretation of secondary remagnetization processes in a way that would be difficult to do for unoriented samples. Examples include the interpretation of magnetizations associated with lightning strikes (Carporzen et al., 2012; Verrier & Rochette, 2002), the measurement of emplacement temperatures of volcanoclastic rocks by analyzing unidirectional thermally induced magnetization overprints after deposition (Lerner et al., 2022), the timing of formation of pigmentary hematite (Swanson‐Hysell et al., 2019), and the timing of diagenetic alteration (Heij & Elmore, 2020). Experience with terrestrial rocks has shown that essentially all of the above paleomagnetic investigations can be achieved with samples whose orientations are estimated with uncertainties ∼3° (Tauxe, 2018).…”
Section: Introductionmentioning
confidence: 99%